Propuesta de una estrategia de fidelización del cliente interno como instrumento para mejorar el ambiente laboral en la Unidad Educativa Corazón de María - Armijos Albán, Lesslie Talia (2015)
This research aims to generate a loyalty strategy to internal customer in “Corazon de Maria” high school. The development of research begins with the collection of theoretical information to support the proposed proposal, issues like human talent management and its six processes, and a legal argument is based on articles of the Constitution of Ecuador, Labour Code and Organic Law of Intercultural Education. In addition to theoretical information, field information was collected through interviews Rector and surveys with internal customers and external customers, all in order to conduct a situational analysis of management developed in “Corazon de Maria” high school. By analyzing the information obtained can detect flaws in Human Resource Management which served as the basis to propose alternatives for improvement in skills development, labor standards and quality of service and remuneration and working conditions. Finally, as a result of this research nine strategies as alternatives for improvement were raised to Human Resource Management at the school.